Infrastructure in informal settlements: co-production of public services for inclusive governance. Issue 12 (1st December 2016) - Otsuki, Kei
ABSTRACT: Recent studies on urban governance have advanced our understanding of how governance could become inclusive through community-based participation in urban development. However, a concrete process by which participatory public service provision in informal settlements consolidates inclusive governance has not been sufficiently evident in the context of the dynamic urban development witnessed in Africa. Drawing on a case study of the informal sanitation infrastructure known as a bio-centre, which has been introduced by a participatory upgrading programme in Nairobi, Kenya, this article proposes to pay attention to ways that informal settlers experience infrastructure, embed it into their everyday context of place-making and use it in unplanned manners. Inclusive governance that is effective in providing public services in informal settlements requires every development actor to be engaged in deliberating how to deal with such unplanned outcomes and eventually to co-produce services. This article argues that, rather than participation, communities' capacity to enrol the state actors in the space of deliberation is crucial to make governance genuinely inclusive.